The Management of Cash Waqf on Dinar and Dirham from The View of Islamic Law (Case study at Wakala Parent Bintan) - Ghozali, Mohammad; Putra, Yoanda Syah (AL-IKTISAB: Journal of Islamic Economic Law, 2019)
Waqf is a struggling conscience to give something to the development of people’s welfare and struggle facilities. Many evidence conveys moving and stationary objects that can be represented but that is not enough to meet the growing needs of society. Based on the principle of waqf is made innovation of waqf products, namely cash waqf, which is with cash funds. The scholars’ past practiced a lot of cash waqf using the dinar and dirham which is currently reappointed by Wakala Parent Bintan. The purpose of this research is to know the theory of Islamic law regarding cash waqf property management, to know the concept and practice of cash, dinar and dirham, to know the Islamic law on the management of cash and dinar Wakalah Parent Bintan. Research method of this study authors using qualitative method, which is a writing aimed at describing and analyzing a phenomenon about what Wakala Parent Bintan did in managing the cash waqf. From this study, researchers concluded that the practice of cash waqf in Wakala Parent Bintan using dinar and dirham, is a cash waqf that replaces it with a stationary object that produces the benefits of education rulings ahlu the madinah is a buy and sell transaction using both dinar and dirham and helps to enrich the surrounding community with market building for merchants without the use of taxes or rental of stalls in the market, as well as build a civilization away from riba. Thus the study can be concluded, but the researcher is aware that the research is far from the word perfection and requires further study that will discuss this issue more clearly. Great researchers hope for the advice and criticism and hopefully this research is beneficial for the authors in particular and the readers in general.